Seven demon stories from medieval Japan - Reider, Noriko T. (Utah State University Press, 2016)
"Seven oni stories from medieval Japan, translated for an English-speaking audience. In Japanese culture, oni are ubiquitous supernatural creatures, some great and some small, some mischievous, others dangerous, who play important roles in literature, lore, and folk belief"--Provided by publisher.